Pemaliq of Sexual Organ within the Culture of Sasak Community: Linguistic Anthropology Study - Suliadi, Suliadi (e-Journal of Linguistics, 2020)
The focus of this study is pemaliq (taboo) of sexual organs within the culture of the Sasak community. This research was conducted with the aims of finding certain words used as an evasion for sexual organs and investigating the Sasak community’s view through the expression of evasion words. The data was collected by applying the method of participant observation and in-depth interviews. The data analysis showed that the evasion words used by the Sasak community for sexual organs are words in the form of euphemisms: pepa (for male and female genitals) and also words in metaphorical form: anak cobek (for male genital), cobek tombong, and dompet (for female genital). The Sasak community believes the use of evasion words in communication can create a psychological comfort and will not make the speakers feel abashed